Restricted Kaposi’s Sarcoma (KS) Herpesvirus Transcription in KS Lesions from Patients on Successful Antiretroviral Therapy - Dirk P. Dittmer (American Society for Microbiology, 2011)
ABSTRACT Kaposi’s sarcoma (KS) is caused by Kaposi’s sarcoma-associated herpesvirus (KSHV; human herpesvirus 8). KS is an AIDS-defining cancer, and it is changing in the post-antiretroviral therapy (post-ART) era. In countries with ready access to ART, approximately one-third of KS cases present in patients with undetectable HIV loads and CD4 counts of ≥200 cells/µl. This is in contrast to pre-ART era KS, which was associated with systemic HIV replication and CD4 counts of ≤200 cells/µl. Using primary patient biopsy specimens, we identified a novel molecular signature that characterizes AIDS KS lesions that develop in HIV-suppressed patients on ART: KSHV transcription is limited in HIV-suppressed patients. With one exception, only the canonical viral latency mRNAs were detectable. In contrast, early AIDS KS lesions expressed many more viral mRNAs, including, for instance, the viral G protein-coupled receptor (vGPCR). IMPORTANCE This is the first genomewide study of Kaposi’s sarcoma-associated herpesvirus (KSHV) transcription in KS lesions in the post-antiretroviral (post-ART) era. It shows that the gene expression of KSHV is altered in patients on ART, and it provides clinical evidence for active AIDS (as characterized by high HIV load and low CD4 counts) being a potential modulator of KSHV transcription. This implies a novel mode of pathogenesis (tightly latent KS), which may inform KS cancer treatment options in the post-ART era.